Valuation of viticultural adaptation to climate change in vineyards: A discrete choice experiment to prioritize trade-offs perceived by citizens - Verónica Farreras; Laura Abraham (Wine Economics and Policy, 2020)
On a climate change scenario, a discrete choice experiment was applied to elicit the trade-off values for three environmental impacts of current viticultural management practices in vineyards of Mendoza, Argentina. Water availability for other uses was found to be the most concerning topic for the population, followed by use of chemical fertilizers and then by use and conservation of biodiversity. An increase of one percentage point in water availability was estimated to add each citizen on average 13.05 Argentinean pesos - 0.74 US dollars - per year in terms of increased welfare, a figure equivalent to the welfare drop a citizen would experience after an increase of 1.45 percentage points in the use of chemical fertilizers annually per hectare, or a decrease of 2.69 percentage points in the use and conservation of biodiversity. These trade-off values may help policy makers, planners, regional managers, and ecologists to take social preferences into account in setting resource allocation priorities intended to support viticulture. This study approach provides a framework that could guide similar assessments in other regions.
Keywords: 330; Viticultural Management Practices; climate change; discrete choice experiment; human welfare effects of environmental-impact choices